Chapter 35 Digital Learning for Developing Asian Countries Achieving equity, quality and efficiency in education - Kumar Bhowmik, Miron (Taylor & Francis, 2018)
Education - that is, the development of knowledge, skills, and values - is an important means by which to empower individuals in a society. As both a means towards and an outcome of gaining the capabilities necessary to participate in and contribute to society, education is an essential enabler in many social aspects, such as economic growth, poverty reduction, public health, and sustainable development, especially in today's knowledge society. At the same time, however, education can still be a social institution that reflects and reproduces the social, cultural, and economic disadvantages that prevail in the rest of society (Bourdieu & Passeron, 1990). For example, students who are discriminated against socio-culturally or who are economically poor are more likely to receive an education that is characterized by inadequate infrastructure, few qualified teachers and encouraging peers, and outmoded pedagogical practices, which often results in a lower quality of life.